Flood Risk Evacuation System in Tanjung Mas, Semarang City - Wungo, Grandy Loranessa; Dewi, Santy Paulla; Mussadun, Mussadun (Faculty of Geography, Universitas Gadjah Mada, 2025)
Rapid urbanization has significantly contributed to environmental degradation, particularly in coastal cities. In Semarang’s Tanjung Mas Village, frequent coastal flooding is a pressing issue, driven by rising sea levels, land subsidence, and inadequate drainage infrastructure. Therefore, this study aims to identify coastal flood hazards in Tanjung Mas and evaluate the efficiency of evacuation routes to improve disaster response strategies. Using GIS-based spatial analysis, flood modeling, and network analysis, high-risk zones, and proposed optimized evacuation pathways are identified. In line with these results, the northern and central sections of Tanjung Mas are the most vulnerable, with densely populated residential and industrial areas at the highest risk. A comparison with Seocho and Gangnam District, South Korea, and Mueang Nakhon Si Thammarat District, Thailand, highlights key differences and similarities. In South Korea and Thailand, the proposed evacuation routes have not adequately considered human behavioral factors. In contrast, a GIS-based specifically tailored to Tanjung Mas, integrating real-time flood updates and optimized route mapping to improve evacuation strategies is proposed. By drawing insights from international case studies, this study contributes to developing adaptive flood evacuation systems applicable to other coastal cities facing similar challenges. These results emphasize the importance of integrating real-time data and community-based planning to enhance disaster resilience and response strategies in urban coastal environments. The approach delivers a novel approach to combining disaster preparedness analysis and flood modeling in the results of a proposed evacuation route in the industrial coastal area.Received: 2024-07-19 Revised: 2024-08-20 Accepted: 2025-03-26 Published: 2025-04-28